PROFITABILITY ANALYSIS OF PADDY RICE MARKETING IN KANO STATE, NIGERIA - Ahmad, M.E.; Onu, J.I.; Lawal, H.; Mohammed, U. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The Study analyzed the profitability of paddy rice marketing in Kano state. A purposively sampling technique was used in selecting 120 paddy rice marketers. Data were collected through the administration of structured questionnaire and analyzed using descriptive statistics and gross margin. The results revealed that paddy rice marketing was a male dominated business (97%) in the study area with majority of the marketers being literate and within the ages of 20-50 years. The results also showed that (28.33%) of the respondents were wholesalers while (49.17%) and (22.25%) were retailers and wholesaler-retailers. The results revealed that gross margins were N642,477.93, N57,355.09 and N485,050.35 for wholesalers, retailers and wholesaler-retailers respectively. Their individual marketing efficiency ratios were 1.06, 1.08 and 1.18 respectively. Insufficient funds for paddy rice marketing was ranked first as the major constraints by both the retailers and wholesalers, while seasonal supply was the first major constraints for the wholesalers. Paddy rice marketing in the study area was a profitable enterprise. It was recommended among others, that the paddy marketers should access formal loans through their cooperative associations to mitigate the problems of insufficient funds they were faced with.